Spatial inequality, geography and economic activity - Sandra Achten; Christian Leßmann (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the effect of spatial inequality on economic activity. Given that the relationship is highly simultaneous in nature, we use exogenous variation in geographic features to construct an instrument for spatial inequality, which is independent from any man-made factors. Inequality measures and instruments are calculated based on grid-level data for existing countries as well as for artificial countries. In the construction of the instrumental variable, we use both a parametric regression analysis as well as a random forest classification algorithm. Our IV regressions show a significant negative relationship between spatial inequality and economic activity. This result holds if we control for country-level averages of different geographic variables. Therefore, we conclude that geographic heterogeneity is an important determinant of economic activity.
Keywords: R12; O15; 330; regional inequality; spatial inequality; economic activity; development; geography; machine learning